The Desistance Journey Into Recovery and Out of Chaos - Cambridge, Graham; Lynch, Orla; Windle, James (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
XI, 168 p. 2 illus., 1 illus. in color.